Sharing and Adaptation of Educational Documents in E-Learning - Abderrahman, Chekry; Aziz, Oriche; Mohamed, Khaldi (International Journal of Emerging Technologies in Learning (iJET), 2012)
Few documents can be reused among the huge number of the educational documents on the web. The exponential increase of these documents makes it almost impossible to search for relevant documents.In addition to this, e-learning is designed for public users who have different levels of knowledge and varied skills so they should be given a content that sees to their needs.This work is about adapting the content of learning with learners preferences, and give the teachers the ability to reuse a given content.